2017
DOI: 10.1186/s13104-017-2524-x
|View full text |Cite
|
Sign up to set email alerts
|

Designing persuasive health materials using processing fluency: a literature review

Abstract: BackgroundHealth materials to promote health behaviors should be readable and generate favorable evaluations of the message. Processing fluency (the subjective experience of ease with which people process information) has been increasingly studied over the past decade. In this review, we explore effects and instantiations of processing fluency and discuss the implications for designing effective health materials. We searched seven online databases using “processing fluency” as the key word. In addition, we gat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 64 publications
(97 reference statements)
0
26
0
2
Order By: Relevance
“…Regarding the manner of writing online pro-vaccine information, studies indicate that anti-vaccine websites are easier to read than pro-vaccine websites [ 37 , 38 , 39 ]. According to psychological research on processing fluency, audiences tend to more readily accept suggestions and are more willing to undertake a suggested action when reading easy-to-read text than text that is difficult to read [ 40 , 41 , 42 ]. Therefore, the ease of readability of online anti-vaccination messages may contribute to readers' acceptance of the anti-vaccination position [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the manner of writing online pro-vaccine information, studies indicate that anti-vaccine websites are easier to read than pro-vaccine websites [ 37 , 38 , 39 ]. According to psychological research on processing fluency, audiences tend to more readily accept suggestions and are more willing to undertake a suggested action when reading easy-to-read text than text that is difficult to read [ 40 , 41 , 42 ]. Therefore, the ease of readability of online anti-vaccination messages may contribute to readers' acceptance of the anti-vaccination position [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, System 1 responds to stimuli possessing cognitive ease such as perceptual, linguistic, and imagery ease ( Kahneman, 2011 ). Therefore, if vaccine recommendation messages use fonts and type sizes that make materials easy to read for perceptual ease, plain language (i.e., common and familiar words, short sentences, explicit sentence constructions) for linguistic ease, and pictures for imagery ease, such pro-vaccination messages may be able to activate System 1 ( Okuhara et al, 2017 ). Studies have shown that a message with high cognitive ease significantly increased self-efficacy ( Okuhara et al, 2020 ), behavioral intention ( Song and Schwarz, 2008 ), and actual behavior ( Okuhara et al, 2018d ) in comparison with a message with low cognitive ease.…”
Section: How To Counter Anti-vaccination Messagesmentioning
confidence: 99%
“…This indicates that perceptual fluency (rather than conceptual fluency) can change according to a type of smartphone application with a different information presentation format. Many extant studies have shown that perceptual fluency influences consumer behaviours (Alter and Oppenheimer, 2009;Okuhara et al, 2017). Perceptual fluency plays an important role in moderating consumers' response to an externally-presented stimulus (Park et al, 2017).…”
Section: The Moderating Effect Of Perceptual Fluency On the Relationsmentioning
confidence: 99%
“…Meanwhile, according to the processing fluency theory (Brakus et al, 2014;Okuhara et al, 2017), perceptual fluency (defined as the ease of perceiving physical features) with a smartphone application may amplify the moderating effect of regulatory focus on the relationship between phone usage and calling plan satisfaction. Specifically, when perceptual fluency is high (vs. low), consumers with a prevention (promotion) focus would have higher satisfaction with a calling plan in case of usage below (above) a preset free allowance.…”
Section: Introductionmentioning
confidence: 99%